2021
DOI: 10.3390/jcm10143191
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health and Psychological Wellbeing during the COVID-19 Lockdown: A Longitudinal Study in the Balearic Islands (Spain)

Abstract: Confining the entire population to a lockdown after the outbreak of SARS-CoV-2 was an unprecedented measure designed to protect the health of those living in Spain. The objective of the present study is to assess the evolution of mental health and psychological wellbeing during lockdown. To do this, we carried out a longitudinal study, via an online survey over the eight weeks of lockdown (weekly assessments). Sociodemographic variables were recorded, along with data related to COVID-19, psychological wellbein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
28
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 52 publications
2
28
1
Order By: Relevance
“…We found no significant differences between gender and family resilience, perceived stress, parental self-efficacy, and marital adjustment. Unlike this study, some studies found differences between females and males (Abdel Jalil et al, 2020 ; Marroquín et al, 2020 ; Ripoll et al, 2021 ).…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…We found no significant differences between gender and family resilience, perceived stress, parental self-efficacy, and marital adjustment. Unlike this study, some studies found differences between females and males (Abdel Jalil et al, 2020 ; Marroquín et al, 2020 ; Ripoll et al, 2021 ).…”
Section: Discussioncontrasting
confidence: 73%
“…Significantly the increase in the symptoms related to anxiety and depression between one and eight weeks was reported. It was especially reported that women over the age of 45, those without a job, and working from home had faced more symptoms of anxiety (Ripoll et al, 2021 ). Another study indicated a temporal increase in anxiety, depression, and stress during the COVID-19 lockdown in a longitudinal study (Planchuelo-Gómez et al, 2020 ).…”
mentioning
confidence: 99%
“…In our study, health-related variables (presence of chronic diseases; taking medication regularly; needing to attend consultations in a health centre, hospital, or clinic regularly; having recently performed COVID-19 tests; and self-assessment of health perception) were related to the presence of psychological distress, as had already been described in the studies by Shehata et al [36], Cybulski et al [37], and Ripoll et al [38]. Regarding the evaluation of the perception of the health of our sample, the results show that the group of people who do not experience psychological distress expressed a better evaluation of their health compared to the group that had psychological distress, although both made a good self-assessment of their health.…”
Section: Discussionsupporting
confidence: 70%
“…Many studies determined that depression reduces satisfaction with life, and a negative relationship was revealed between them [77,86,88,89]. Moreover, the current literature has confirmed that the level of satisfaction with life decreased with the increase of depression of all segments of society, especially during extraordinary periods such as the COVID-19 pandemic [90][91][92].…”
mentioning
confidence: 82%